Implementation of Edutainment-Based Learning Centers to Improve Children's Interpersonal Intelligence - Nesna Agustriana; Nina Kurniah; Alexon Alexon; Rambat Nur Sasongko; Raden Gamal Tamrin Kusumah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Intelligence does not only lie in cognitive, but interpersonal is a form of multiple intelligences. This research is based on learning centers in several kindergarten in Bengkulu whose implementation is still very varied. This research was conducted on children at Kindergarten IT Auladuna Bengkulu by applying edutainment-based learning centers. This school was chosen because the implementation of the learning center was in accordance with the guidelines approved by the Ministry of Education and Culture. The research design used was a one group pretest-posttest design. Data were taken by pretest and posttest in the experimental class and the control class. The results showed that the application of edutainment-based learning centers had a significant N-Gain effectiveness. The result is an average of 78.99% which is high when compared to the control class learning (mean 23.03%) carried out in that school. So it can be concluded that the application of edutainment-based learning centers has been effective in improving children's interpersonal intelligence.